THE IMPLEMENTATION OF AN INDIVIDUALIZED EDUCATION PROGRAM FOR STUDENTS WITH SPECIAL NEEDS IN ISLAMIC ELEMENTARY SCHOOLS - Priatmoko, Sigit; Salsabila, Helga; Sugiri, Wiku Aji; Amelia, Rizki; Hilmi, Annafik Fuad (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Many students with special needs have difficulty participating in classroom learning because the school has not properly accommodated them. This research explores how MIT (Madrasah Ibtidaiyah Terpadu) Ar-Roihan accommodates special student needs by implementing an individual learning model. This research uses a qualitative approach by employing case studies. The data collection process uses non-participant observation, semi-structured interviews, and documentation. Researchers use an interactive analysis model, including data collection, condensation, presentation, and conclusion to analyze the data. To ensure the validity of the data, researchers applied source and method triangulation techniques. The research results show that the preparation and implementation of the Individualized Education Program (IEP) at MIT Ar-Roihan has fulfilled the rules for preparing an IEP; this can be seen when the IEP is compared with the sample IEP recommended by the National Council for Special Education (NCSE). However, several aspects require more attention from MIT Ar-Roihan, especially in identifying resources and strategies needed for learning and regular IEP review mechanisms to improve the quality of learning for students with special needs that researchers have not found explicitly in the steps -steps in preparing an IEP. Apart from that, the learning indicators included in the IEP still look the same as those for regular students.